2014
DOI: 10.4238/2014.november.28.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of BMPRIB gene silencing by siRNA on apoptosis and steroidogenesis of porcine granulosa cells

Abstract: ABSTRACT. Bone morphogenetic proteins (BMPs) are the key factors in maintaining cell growth and differentiation in ovaries. BMPs initiate signaling by assembling BMP receptors and activating Smads, which in turn alter the expression of target genes. However, little is known about the effect of the deletion of the Bone morphogenetic protein receptor type IB (BMPRIB) on porcine granulosa cell (GCs). The objective of this study was to determine the effects of BMPRIB gene silencing, by small interfering RNA (siRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…Our result was consistent with the findings of Silva et al 36 , reported the expression of BMPRs in granulosa cells of antral follicles in goat. Significantly (p < 0.05) higher abundance of BMPR-IB mRNA in granulosa cells obtained from large antral follicles was found in our study is in accordance to earlier reports in goat, pig and buffalo [37][38][39] . The expression of BMPRs in the follicle suggests the potential role of BMP system in affecting the steroidogenesis and functional differentiation of granulosa cells.…”
Section: Discussionsupporting
confidence: 93%
“…Our result was consistent with the findings of Silva et al 36 , reported the expression of BMPRs in granulosa cells of antral follicles in goat. Significantly (p < 0.05) higher abundance of BMPR-IB mRNA in granulosa cells obtained from large antral follicles was found in our study is in accordance to earlier reports in goat, pig and buffalo [37][38][39] . The expression of BMPRs in the follicle suggests the potential role of BMP system in affecting the steroidogenesis and functional differentiation of granulosa cells.…”
Section: Discussionsupporting
confidence: 93%
“…BMPRIB in mouse was demonstrated to involve in estrus cyclicity, estradiol biosynthesis, and cumulus cell expansion in vivo (Soyun et al, 2001). Similar results are reported in the study of pig and ewe (Mulsant et al, 2001;Zhao et al, 2014). As a consequence, BMPRIB of S. paramamosain might regulate vitellogenesis in the ovary.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, Sp-BMPRIB and Sp-BMPRII had an abundant expression in ovary as well as Sp-BMP7. The higher expression of some BMP ligands and receptors in ovary has been reported in many mammals, such as goat (Lima et al, 2012), hamster (Lima et al, 2012) and swine (Zhao et al, 2014). Thus, the results of tissues distribution, especially the abundant expression of BMP system in ovarian development attracted our attention.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations